Enhancing baculoviral infectivity by expressing polyhedrin protein fused with Bacillus thuringiensis Cry1D toxin - Abdul Aziz, Hamzah (2014)
Escherichia coli and baculovirus are the common commercially available vectors used for protein expression. Both allow expression of huge amount of heterologous proteins which are functionally similar to the native proteins. The cry1D gene of Bacillus thuringiensis subsp. aizawai was successfully cloned into TA cloning vector and pBACgus-2cp EK/LIC baculovirus expression vector, and expressed in E. coli BL21 and Trichoplusia ni cells, respectively. Negative results were obtained when expressed in Sf9 (Spodoptera frugiperda cell line) and TUAT-Spli-221 (Spodoptera litura cell line). The sequence identity of the 3.5 kb DNA insert was compared with other holotype cry1D genes and scored 100% sequence similarity with cry1Da1 and cry1Da2 genes. A 140 kDa protein was produced by the recombinant baculovirus (AcMNPV) and cross-reacted with His-Tag monoclonal antibodies in Western blot analysis. The insecticidal activity of the recombinant AcMNPV and the Cry1D protoxin expressed in E. coli cells was compared against S. litura and S. exigua. The recombinant AcMNPV was injected into third instar Spodoptera exigua larvae (the dose is equivalent to2 x 105 pfu) and the median lethal time (LT50) of infected S. exigua larvae was approximately 70% shorter than that of the wild-type AcMNPV. This recombinant AcMNPV was unable to induce mortality in the second instar larvae of S. litura. In contrast, the Cry1D protoxin expressed in E. coli cells appeared to have higher toxicity against S.litura (LT50 = 4.14 days) than S. exigua (LT50 = 10.65 days). This protoxin induced lower toxicity against susceptible insect host when compared to the commercial Bt Flobac. This may be due to the instability of the Cry1D protoxin when expressed in vitro in E. coli cells. The recombinant AcMNPV only expressed Cry1D protoxin when replicating in the susceptible insect cells, thus the protoxin was stable within the susceptible insect and able to induce higher toxicity in S. exigua when compared to the commercial Bt Flobac. The wild-type AcMNPV was unable to infect S. litura in this study, thus the efficacy of the recombinant AcMNPV against S. litura could not be compared with those Cry1D protoxin expressed in E. coli cells. Experiments were also conducted to study whether the truncated-core active part of cry1D gene expressed in both E. coli and BEVS could induce mortality in S. litura and S. exigua. The truncated-core active Cry1D toxin was successfully expressed in E. coli cells but not in T. ni cells. However, negative response was recorded in both S. exigua and S. litura larvae when challenged with the truncated-core active Cry1D toxin. Therefore, the fusion of Cry1D protoxin into baculovirus was proven able to improve its efficacy as a biopesticide.